GW24-e1194 The proarrhythmic action of Fluconazole and the underlying mechanism. (1st October 2013) - Jinli, Wang; Zhang, Cuntai; Wang, Guan; Liu, Yang; Zhao, Junyan; Quan, Xiaoqing; Ruan, Lei; Bai, Rong
Abstract : Objectives: To investigate the proarrhythmic action of fluconazole and the underlying mechanism. Methods: Twenty Japanese long-eared white rabbits were randomly distributed into Normal group and Fluconazole group, the Normal group were treated with 0.5% sodium carboxymethyl cellulose and the Fluconazole group were treated with fluconazole; the ECG were recorded during the period. Artery-perfused rabbit left ventricular preparation were made two weeks later, volume ECG, action potential from both endocardium and epicardium and the arrhythmia events were recorded. The changes of HERG protein expression were measured by Western blot. Results: Fluconazole group had a longer QT interval being treated one week later (p < 0.05) and a higher arrhythmia occurrence two weeks later (p < 0.05); compared with Normal group, Fluconazole group showed a longer Epi-APD and TDR and a higher TdP occurrence in Artery-perfused left ventricular preparation; also, Western blot results showed that the density of HERG protein in cytoplasm was higher than Normal group. Conclusions: Fluconazole can prolonged the QT interval and had potential proarrhythmic action by leading to HERG protein trafficking deficiency, thus we must pay attention on it in clinical using.